Carbon-enhanced lithium-carbon composite electrode with lithium-loving characteristic and preparation method of carbon-enhanced lithium-carbon composite electrode

A carbon-enhanced lithium-carbon composite electrode using a tin medium addresses the stability and efficiency issues of lithium deposition, achieving high specific capacity and stability through controlled lithium deposition and reduced dendrite formation.

CN119230762AInactive Publication Date: 2024-12-31SANYA INST OF OCEANOGRAPHY OCEAN UNIV OF CHINA +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746403.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium metal negative electrodes in lithium-ion batteries face challenges such as heterogeneous lithium deposition, dendrite growth, and poor Coulombic efficiency, limiting their widespread application due to the difficulty in forming a stable lithium deposition on carbon surfaces, and silver plating methods are costly and difficult to implement effectively.

Method used

A carbon-enhanced lithium-carbon composite electrode is prepared using a tin medium with high lithium affinity, forming a C-Sn matrix through methods like melt impregnation and redox processes, which promotes stable lithium deposition and reduces dendrite formation.

Benefits of technology

The composite electrode achieves high specific capacity, excellent cycle stability, and low overpotential, with improved lithium affinity and electrochemical performance, overcoming the limitations of silver plating and conventional carbon electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230762A_ABST
    Figure CN119230762A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a carbon-enhanced lithium-carbon composite electrode with a lithium-loving characteristic and a preparation method thereof. The method comprises the following steps: 1) preparing elemental tin on a carbon carrier to obtain a C-Sn carrier; (2) the C-Sn carrier is used as a raw material to be manufactured into a sheet shape or a paper shape, and a C-Sn base body is obtained; and (3) immersing the C-Sn matrix into molten lithium in a protective atmosphere, standing, preserving heat, taking out, and cooling to obtain the carbon-reinforced lithium-carbon composite electrode with the lithium-loving characteristic. According to the invention, Sn is used as a medium, so that the C-Li combination problem is effectively improved, effective preparation of the lithium-carbon composite electrode is realized, and the formed composite electrode has an extremely large specific surface area, extremely abundant lithium-loving point locations, good electrochemical performance and stable mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties and a preparation method thereof. Background Art

[0002] Lithium-carbon electrodes, as negative electrode materials for lithium-ion batteries, have important research and application backgrounds. Lithium metal negative electrodes are regarded as strong competitors for the next generation of lithium-ion batteries due to their low redox potential and ultra-high theoretical specific capacity (about 3860 mAh / g). However, there are some challenges in the practical application of lithium metal negative electrodes, including heterogeneous lithium deposition, dendrite growth, and poor Coulombic efficiency, which limit their widespread application in battery technology.

[0003] To address these issues, researchers have been exploring ways to combine carbon materials with lithium metal. Carbon materials are considered viable hosts for stabilizing lithium metal due to their light weight, high conductivity, and tunable physicochemical properties. By designing three-dimensional carbon materials with a large number of lithiophilic sites and a large specific surface area, the lithium deposition kinetics can be controlled, promoting the rapid flow and nucleation of lithium ions, and mitigating the formation of lithium dendrites.

[0004] However, it is extremely difficult to form a stable lithium deposition on the carbon surface. Because the carbon material itself is not very lithium-affinity, the deposition of lithium metal on its surface is often uneven, and dendrites are easily generated, which will reduce the safety and cycle stability of the battery, which leads to the difficulty of preparing lithium-carbon composite electrodes. At present, in order to solve this problem, the commonly used method is to prepare and form a medium. Currently known effective media include silver media, such as the article Electrodeposition behavior of lithium metal on carbon substrates with surfacesilvering, November 2019, Pages 503-510 published by Ran Tian, ​​which reveals a phenomenon and effect of changing the electrodeposition behavior of lithium metal by silver plating on the surface of a carbon carrier, promoting uniform deposition and inhibiting the formation of dendrites. However, silver plating deposition still has certain defects. First, silver plating is difficult and costly. Second, silver itself is not an active material for the negative electrode of a lithium battery, and it is difficult to improve the theoretical specific capacity to improve battery performance. Moreover, in comparison, silver is usually difficult to load onto micro-nano scale carbon carriers because of its high melting point. Loading can be achieved by methods such as melt immersion plating, while chemical plating loading is difficult to control to form smaller loaded particles. Instead, it is easy to form large-scale agglomerates or directly wrap the carbon carrier.

[0005] In this regard, technicians have conducted more research. After research, it was found that because tin metal has a higher affinity with lithium than silver, it can form a variety of Li-Sn alloy phases, such as Li22Sn5, and actually shows a stronger ability to promote lithium diffusion and alloying, which can significantly increase the lithium content of the composite negative electrode and significantly improve the lithium affinity of the composite electrode, thereby significantly improving the electrode performance. Therefore, it has extremely high research value. Summary of the invention

[0006] In order to solve the many usage defects of the existing lithium metal negative electrode, although the lithium carbon electrode has good theoretical performance, it is difficult to stably form lithium metal deposition on the carbon surface, and the silver medium is expensive and its use is relatively limited. The present invention provides a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, and a preparation method of the composite electrode.

[0007] The main purpose of the present invention is: 1. Using a new type of metal medium to realize Li-C composite construction of lithium-carbon composite electrode with extremely strong lithium affinity; Second, it can effectively realize the coordination between carrier carbon and medium; 3. Ensure that the constructed lithium-carbon composite electrode has good lithium affinity and electrochemical performance; 4. The preparation method is simple, efficient and low-cost.

[0008] To achieve the above objectives, the present invention adopts the following technical solutions.

[0009] A method for preparing a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, The method comprises: 1) Prepare tin element on a carbon support to obtain a C-Sn support; 2) Using C-Sn carrier as raw material to make it into thin sheets or paper to obtain C-Sn matrix; 3) Immerse the C-Sn substrate into molten lithium in a protective atmosphere, let it stand and keep warm, then take it out and cool it to obtain a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties.

[0010] As a preference, Step 1) The carbon carrier is micron-sized and / or nano-sized carbon tubes and / or carbon powder.

[0011] As a preference, Step 1) The method for preparing the tin element is a melt impregnation method and / or a chemical deposition method and / or an oxidation-reduction method; in: The melt impregnation process is as follows: in a protective atmosphere, a carbon carrier is added to molten tin, stirred and kept warm for 1 to 20 minutes, the carbon carrier is filtered out and cooled, so that the surface of the carbon carrier solidifies to form a tin element load to obtain a C-Sn carrier; The chemical deposition method is reduction chemical tin plating and / or disproportionation reaction chemical tin plating and / or immersion chemical tin plating and / or acid tin plating and / or alkaline tin plating; As the chemical deposition methods are conventional lithium plating methods, they are recorded in many prior arts, and therefore, except for the specific mention in the embodiments, they will not be described in detail, and the chemical deposition methods mentioned above are all feasible to use micro-nano materials as deposition carriers; The redox process is as follows: immersing the carbon carrier into a tin salt solution, immersing under negative pressure for 30 to 90 minutes, filtering and transferring to a protective atmosphere for carbon thermal reduction reaction for 30 to 90 minutes, and then cooling to obtain a C-Sn carrier.

[0012] As a preference, Step 2) The raw material is manufactured into a sheet or paper form by using a papermaking method and / or a suction filtration method.

[0013] As a preference, Step 2) The thickness of the C-Sn substrate is ≤3 mm.

[0014] As a preference, Step 3) immersing the C-Sn substrate into molten lithium and keeping the temperature for 1 to 20 minutes.

[0015] A carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, The composite electrode uses a carbon carrier to construct a two-dimensional and / or three-dimensional micro-nano structure, and a tin-lithium alloy is loaded on the basis of the micro-nano structure to form a cross-scale multi-dimensional structure.

[0016] The technical solution of the present invention adopts the construction form of C-Sn-Li, with Sn metal as the medium for Li-C connection. Since Sn has very excellent lithium affinity, Li metal can be very effectively and stably deposited on the surface of the carbon carrier, and has an extremely high deposition amount, thereby having excellent conductivity, lithium affinity and electrochemical properties.

[0017] Specifically, The present invention first adopts some methods to realize the construction and preparation of C-Sn carrier. For conventional carbon carriers, such as carbon cloth and carbon paper, conventional and efficient evaporation methods can be used to deposit and plate tin metal, but for micro-nano scale carbon carriers, chemical deposition methods are usually required for plating. However, as a conventional plating method, chemical deposition methods, although having technical maturity and a high degree of industrialization, show relatively limited plating effects. Because the carbon carrier used in the present invention is a relatively special carbon nanotube, it can be selectively matched with carbon nanopowder and / or carbon micron powder, that is, the most core carbon carrier is carbon nanotube, because carbon nanotube is a one-dimensional structure with a cavity, it can effectively form a cross-scale three-dimensional structure in the subsequent film-making process, and has a large specific surface area, which can provide more active sites to improve the electrochemical performance of the electrode. In addition, compared with other C and / or Si system negative electrode materials, carbon nanotubes have a more unique tubular structure, resulting in higher strength and toughness, and can resist the stress caused by volume changes during charging and discharging, and reduce the volume change rate. However, for conventional chemical deposition methods, it is usually difficult to effectively achieve deposition on the inner surface of the tube, and the deposition uniformity is relatively difficult to control. Figure 1 Therefore, for the technical solution of the present invention, it is relatively better to use the melt dipping method and / or the redox method for tin plating.

[0018] For the melt impregnation method, since tin has a low melting point, it can be heated to a molten state and then the carbon carrier can be immersed in the molten tin in a protective atmosphere. Then, the carbon carrier is kept warm for a period of time so that it is fully infiltrated by the molten tin, filtered, and cooled to solidify to form a tin load. This form can be as follows Figure 2 As shown, tin is continuously solidified and coated on the surface of the carbon carrier. This form of tin loading is large and uniform, and a certain degree of effective loading can also be formed on the inner wall surface of the carbon nanotube. The loading is more thorough, stable and has strong binding force.

[0019] The redox method is an original tin metal loading method of the present invention based on the technical purpose of the present invention. The core is to first form a tin salt and / or tin oxide loading and finally realize the conversion into a tin oxide loading. Here, the tin oxide is usually SnO2. After the loading is completed, a carbon thermal reduction reaction is carried out in a protective atmosphere. In this process, it can be reduced in situ to form a metallic tin element and diffuse at the same time. However, the diffusion process is relatively unidirectional. Because tin is a larger atom and the lattice gap of the carbon material is smaller, tin usually does not enter the lattice of the carbon material through the gap diffusion mechanism. Carbon atoms, as smaller atoms, can diffuse in the lattice of tin through the gap diffusion mechanism. This diffusion process can make the degree of combination of tin and carbon higher, and because tin has the characteristics of low melting point and high boiling point, it will not be vaporized in the process under appropriate temperature conditions. Instead, it will be more evenly and stably coated on the carbon nanotubes due to the liquid capillary effect and the carbon diffusion effect, forming a structure such as Figure 3 The Sn / C diffusion layer formed by carbon diffusion also forms more active sites, which further improves the performance of the electrode. In the subsequent lithium diffusion process, the redox method also shows very different uniqueness.

[0020] Because the diffusion of lithium itself in the tin element has two diffusion forms, namely vacancy diffusion and interstitial diffusion, and these two diffusion forms compete with each other. This leads to a certain volatility of lithium diffusion. However, this has not changed for the elemental lithium obtained by melt impregnation and chemical deposition, and the two compete with each other, and the important Li22Sn5 phase, as a key phase component that significantly affects the electrode performance, is an important product of interstitial diffusion. Generally speaking, the diffusion of solid carbon and solid tin will be mainly based on interstitial diffusion, which increases the vacancy of the tin coating to a certain extent, but the carbon and tin of the present invention are solid-liquid diffusion forms, which changes the diffusion form between carbon and tin, which leads to a certain decrease in the vacancy concentration in the tin coating, so that the Li22Sn5 formed in the subsequent molten lithium immersion plating process is more, further improving the performance of the composite electrode.

[0021] Moreover, the formed lithium-carbon composite electrode has a large number of lithium-philic sites and a three-dimensional structure with a large specific surface area, which can control the lithium deposition kinetics, promote the rapid flow and nucleation of lithium ions, and reduce the formation of lithium dendrites.

[0022] On the other hand, in the technical solution of the present invention, the preparation process of step 2) is also different. The present invention adopts suction filtration to make paper or conventional carbon fiber papermaking technology to manufacture a sheet-like (i.e., thin sheet or paper-like) substrate. In this process, high temperature and high pressure should be strictly avoided. High temperature will cause the diffusion process on the Sn-C carrier to occur further, which may cause the interstitial concentration in the tin-plated layer to decrease and the vacancy concentration to increase, and the subsequent lithium deposition and diffusion effect will be weakened. High pressure (such as pressing operations) will directly cause the three-dimensional structure of the C-Sn carrier to collapse, resulting in the transformation of the three-dimensional structure to a two-dimensional structure, reducing the active lithium-philic sites and specific surface area, which will have significant adverse effects.

[0023] The beneficial effects of the present invention are: The present invention effectively improves the C-Li bonding problem by using Sn as a medium, and realizes the effective preparation of a lithium-carbon composite electrode. The formed composite electrode has a large specific surface area, extremely abundant lithium-philic sites, good electrochemical properties and stable mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the construction of C-Sn support for chemical deposition method; Figure 2 Schematic diagram of the construction of C-Sn support by melt impregnation method; Figure 3 Schematic diagram of the construction of C-Sn support for redox method; Figure 4 This is a microstructure characterization diagram of the original carbon nanotubes in Example 1; Figure 5 This is a microstructure characterization diagram of the product prepared by chemical deposition method in Example 1; Figure 6 This is a microstructural characterization diagram of the product prepared by the redox method in Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0026] In the description of the present invention, it should be understood that the terms "thickness", "upper", "lower", "horizontal", "top", "bottom", "inner", "outer", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined, and "several" means one or more.

[0027] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0028] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0029] Example 1 A method for preparing a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, The method comprises: 1) Using carbon nanotubes (model TNM0) as carbon carriers, tin was prepared on the carbon carriers; Prepared by the following methods: Melt impregnation method: In a nitrogen atmosphere, add the carbon carrier to molten tin at 260 °C, stir and keep warm for 10 min, then filter out the carbon carrier and cool it down to solidify the surface of the carbon carrier to form a single tin load to obtain C-Sn carrier-Dp; Chemical deposition method: The carbon carrier is added to a 1.0 mol / L sodium hydroxide solution at a ratio of 1 g:20 mL for ultrasonic cleaning. After filtering and drying, the washed carbon carrier is added to a tin plating solution at a ratio of 1 g:20 mL. The tin plating solution contains 1.0 mol / L SnCl2, 1.0 mol / L HCHO, and 0.5 mol / L sodium tartrate, and the pH value is adjusted to 2 with dilute hydrochloric acid. After keeping warm at 60°C for 15 min, the solution is filtered, washed, and dried to obtain C-Sn carrier-Ch; Redox method: The carbon carrier was added to a 1.0 mol / L sodium hydroxide solution at a ratio of 1 g:20 mL for ultrasonic cleaning. After filtration and drying, the washed carbon carrier was added to a 0.5 mol / L SnCl4 aqueous solution at a ratio of 1 g:30 mL. After immersion for 60 min under a negative pressure of 0.2 atm, the carbon carrier was filtered and transferred to a vacuum reactor. After evacuation to ≤100 Pa, the temperature was raised to 1350 °C for carbon thermal reduction and kept warm for 60 min. After cooling with the furnace, C-Sn carrier-Re was obtained. 2) Using C-Sn carrier (including C-Sn carrier-Dp, C-Sn carrier-Ch and C-Sn carrier-Re) as raw material, the paper-like material was manufactured by suction filtration, and the pressure of the suction filtration process was controlled at -50 kPa, to obtain a C-Sn matrix with a thickness of about 80 μm, which were marked as C-Sn matrix-Dp (corresponding to C-Sn carrier-Dp obtained in step 1), C-Sn matrix-Ch (corresponding to C-Sn carrier-Ch obtained in step 1) and C-Sn matrix-Re (corresponding to C-Sn carrier-Re obtained in step 1)); 3) The C-Sn substrate was immersed in molten lithium at 220 °C in a vacuum furnace, and after standing and keeping warm for 20 min, it was taken out and cooled to obtain a carbon-reinforced lithium-carbon composite electrode with lithium-philic properties, which were marked as electrode-Dp (corresponding to the C-Sn substrate-Dp prepared in step 2), electrode-Ch (corresponding to the C-Sn substrate-Ch prepared in step 2) and electrode-Re (corresponding to the C-Sn substrate-Re prepared in step 2).

[0030] The obtained carbon-enhanced lithium-carbon composite electrode with lithium-philic properties was characterized by microstructure and performance. Figures 4 to 6 As shown. Figure 4 This is a microstructure characterization diagram of the original carbon nanotubes. Figure 5 This is a microstructural characterization of the final product obtained by chemical deposition. Figure 6 Figure 2 is a microstructure characterization diagram of the final product obtained by the redox method. Figures 4 to 6 It can be clearly seen that different methods of Sn loading have a great impact on the structure of the product. When prepared by the redox method, the structural characteristics of the original carbon nanotubes can be retained to a greater extent, while the chemical deposition method will obviously form island-shaped, block-shaped deposition and blockage, resulting in a significant change in the overall structure.

[0031] Additionally, performance characterization includes: Specific capacity characterization, cycle stability (500 cycle retention rate), coulombic efficiency and overpotential characterization were carried out at current density of 0.1 A / g, 0.5 A / g and 2.0 A / g, respectively.

[0032] The performance characterization results are shown in the following table.

[0033]

[0034] From the above characterization results, the composite electrode of the present invention has extremely excellent electrochemical properties. First, it exhibits extremely high specific capacity, which is much higher than the common tin-based lithium ion electrode (i.e., tin dioxide-loaded lithium electrode, which usually has a specific capacity of about 780 mAh / g under 0.1 A / g test conditions), and has extremely high cycle stability and coulombic efficiency, and exhibits very low overpotential, indicating that the formation of lithium dendrites is significantly suppressed, and has extremely high stability and safety.

[0035] However, it can be seen from the comparison in the above table that different methods for preparing carriers will also bring about significant differences in electrode performance. For example, the performance of the electrode-Ch obtained by the chemical deposition method is relatively the worst. Although it is also superior to tin-based lithium-ion batteries to a certain extent, because the actual present invention introduces metallic lithium to form a Li22Sn5 alloy phase, the alloy phase can significantly optimize the performance of the electrode, but because the amount of introduction is relatively limited, the amount of lithium element introduced in step 3) is calculated by mass difference as electrode-Re>electrode-Dp>electrode-Ch, but the proportion of lithium is not high (all ≤3.6 wt%), so it is not appropriate to compare directly with the lithium metal electrode. In addition, the crystal structure and phase composition analysis of the tin-lithium alloy layer formed in step 3) show that the proportion of the Li22Sn5 alloy phase is also electrode-Re>electrode-Dp>electrode-Ch, which is positively correlated with the above-mentioned amount of lithium element introduction, which is also in line with expectations. It also proves that the Li22Sn5 alloy phase is an important component affecting the electrochemical properties of the electrode.

[0036] Example 2 A method for preparing a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, The method comprises: 1) Using carbon nanotubes (model TNM0) as carbon carriers, tin was prepared on the carbon carriers; Prepared by the following methods: Melt impregnation method: In a nitrogen atmosphere, add the carbon carrier to molten tin at 260 °C, stir and keep warm for 10 min, then filter out the carbon carrier and cool it down to solidify the surface of the carbon carrier to form a single tin load to obtain C-Sn carrier-Dp; Chemical deposition method: The carbon carrier is added to a 1.0 mol / L sodium hydroxide solution at a ratio of 1 g:20 mL for ultrasonic cleaning. After filtering and drying, the washed carbon carrier is added to a tin plating solution at a ratio of 1 g:20 mL. The tin plating solution contains 1.0 mol / L SnCl2, 1.0 mol / L HCHO, and 0.5 mol / L sodium tartrate, and the pH value is adjusted to 2 with dilute hydrochloric acid. After keeping warm at 60°C for 15 min, the solution is filtered, washed, and dried to obtain C-Sn carrier-Ch; Redox method: The carbon carrier was added to a 1.0 mol / L sodium hydroxide solution at a ratio of 1 g:20 mL for ultrasonic cleaning. After filtration and drying, the washed carbon carrier was added to a 0.5 mol / L SnCl4 aqueous solution at a ratio of 1 g:30 mL. After immersion for 60 min under a negative pressure of 0.2 atm, the carbon carrier was filtered and transferred to a vacuum reactor. After evacuation to ≤100 Pa, the temperature was raised to 1350 °C for carbon thermal reduction and kept warm for 60 min. After cooling with the furnace, C-Sn carrier-Re was obtained. 2) Using C-Sn carrier (including C-Sn carrier-Dp, C-Sn carrier-Ch and C-Sn carrier-Re) as raw materials, the paper-like material was manufactured by suction filtration, and the pressure of the suction filtration process was controlled at -50 kPa, to obtain a C-Sn matrix with a thickness of about 1.5 mm, which were marked as C-Sn matrix-Dp (corresponding to C-Sn carrier-Dp obtained in step 1), C-Sn matrix-Ch (corresponding to C-Sn carrier-Ch obtained in step 1) and C-Sn matrix-Re (corresponding to C-Sn carrier-Re obtained in step 1)); 3) The C-Sn substrate was immersed in molten lithium at 220 °C in a vacuum furnace, and after standing and keeping warm for 20 min, it was taken out and cooled to obtain a carbon-reinforced lithium-carbon composite electrode with lithium-philic properties, which were marked as electrode-Dp (corresponding to the C-Sn substrate-Dp prepared in step 2), electrode-Ch (corresponding to the C-Sn substrate-Ch prepared in step 2) and electrode-Re (corresponding to the C-Sn substrate-Re prepared in step 2).

[0037] The performance of the obtained carbon-enhanced lithium-carbon composite electrode with lithium-philic properties was characterized.

[0038] Signs include: Specific capacity characterization, cycle stability (500 cycle retention rate), coulombic efficiency and overpotential characterization were carried out at current density of 0.1 A / g, 0.5 A / g and 2.0 A / g, respectively.

[0039] The characterization results are shown in the following table.

[0040]

[0041] From the above characterization results, as the matrix is ​​prepared by filtration in step 2), the thickness of the matrix increases and the performance of the electrode decreases. This is mainly due to the preparation method of the present invention, because the process of converting the matrix into an electrode is formed by infiltration in molten lithium, and the actual fluidity and immersion depth of molten lithium are very limited. As the thickness increases, the difficulty of infiltration will gradually increase. Although increasing the temperature of molten lithium can improve its fluidity to a certain extent, the melting point of tin is not high. Excessive molten lithium temperature will cause the distribution morphology of tin to change, and even cause the melting of tin to cause the affinity of the matrix to lithium to weaken. Therefore, for the technical solution of the present invention, the thickness of the matrix should be controlled. After testing, when the thickness of the matrix reaches about 3 mm, the minimum specific capacity (i.e., 3 mm thickness electrode-Dp) of the prepared electrode under the current density test condition of 0.1 A / g can still reach about 961 mAh / g, and when the thickness is further increased to about 3.5 mm, it will drop sharply to about 802 mAh / g, so the situation where the thickness of the matrix is ​​controlled to ≤3 mm is relatively optimal. Ultra-thin substrates can be used for ultra-thin sheet battery electrodes, while thick substrates can be used to prepare large single-cell battery electrodes.

[0042] Example 3 A method for preparing a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties, based on Example 1, only the melt impregnation method and the redox method in step 2) are adjusted to prepare C-Sn carrier-Dp under different holding time conditions, and C-Sn carrier-Re under different impregnation time and thermal reduction time conditions; Specifically include: 1) Using carbon nanotubes (model TNM0) as carbon carriers, tin was prepared on the carbon carriers; Prepared by the following methods: Melt impregnation method: In a nitrogen atmosphere, add the carbon carrier to molten tin at 260 °C, stir and keep warm, filter out the carbon carrier and cool it, so that the surface of the carbon carrier solidifies to form a single tin load to obtain C-Sn carrier-Dp; Redox method: The carbon carrier was added to a 1.0 mol / L sodium hydroxide solution at a ratio of 1 g:20 mL for ultrasonic cleaning. After filtration and drying, the washed carbon carrier was added to a 0.5 mol / L SnCl4 aqueous solution at a ratio of 1 g:30 mL. After immersion for 60 min under a negative pressure of 0.2 atm, the carbon carrier was filtered and transferred to a vacuum reactor. After evacuation to ≤100 Pa, the temperature was raised to 1350 °C for carbon thermal reduction and kept warm for 60 min. After cooling with the furnace, C-Sn carrier-Re was obtained. 2) Using C-Sn carrier (including C-Sn carrier-Dp and C-Sn carrier-Re) as raw material, the paper is made by filtration, and the pressure of the filtration process is controlled at -50 kPa to obtain a C-Sn matrix with a thickness of about 80 μm, which are marked as C-Sn matrix-Dp (corresponding to C-Sn carrier-Dp obtained in step 1) and C-Sn matrix-Re (corresponding to C-Sn carrier-Re obtained in step 1)); 3) The C-Sn substrate was immersed in molten lithium at 220 °C in a vacuum furnace, and after standing and keeping warm for 20 min, it was taken out and cooled to obtain a carbon-reinforced lithium-carbon composite electrode with lithium-philic properties, which were marked as electrode-Dp (corresponding to the C-Sn substrate-Dp prepared in step 2) and electrode-Re (corresponding to the C-Sn substrate-Re prepared in step 2) respectively.

[0043] The performance of the obtained carbon-enhanced lithium-carbon composite electrode with lithium-philic properties was characterized.

[0044] Signs include: 0.1 A / g specific capacity characterization, 0.1 A / g cycle stability (500 cycle retention rate).

[0045] The characterization results are shown in the following table.

[0046]

[0047] From the above characterization results, the electrode Dp will significantly increase the specific capacity of the final electrode product as the insulation immersion time in molten tin increases, but its cycle stability also decreases as the insulation time increases. This is because during the molten impregnation process, as the immersion time increases, more metal tin can be impregnated and loaded, increasing the loading amount of metal tin, but due to the limitation of the carrier, its actual loading amount is relatively limited. Therefore, in the range of 30 s to 20 min, as the time increases, the electrode specific capacity can be significantly improved, but in the range of 20 to 25 min, its loading amount may be limited by the structure of the carrier and cannot continue to increase. For cycle stability, the carbon carrier structure is more important. Under too long an immersion, due to the high density of molten tin, it forms a certain extrusion burden on the carbon carrier. Too long an immersion load may cause its structure to collapse, which ultimately leads to a decrease in its cycle stability.

[0048] As for the redox product, the loading amount of tin compound can be increased with the extension of impregnation time, but similarly, in the impregnation process, vacuum impregnation can ensure a better impregnation effect, so too long impregnation will also cause the structure of the carbon carrier to collapse to a certain extent, resulting in a decrease in cycle stability. In the carbon thermal reduction process, the thermal reduction process usually does not affect the structure of the carbon carrier, but due to the high problem, short-term reduction and heat preservation will lead to a low degree of reduction, making it difficult to effectively achieve tin reduction. If the reduction and heat preservation time is too long, it will lead to the loss of metal tin after reduction, resulting in a decrease in specific capacity, so the reduction time also needs to be controlled.

[0049] Comparative Example 1 A method for preparing a carbon-enhanced lithium-carbon composite electrode, The method comprises: 1) Using carbon nanotubes (model TNM0) as raw materials, the paper was made by filtration. The pressure during the filtration process was controlled at -50 kPa, and a C matrix with a thickness of about 80 μm was obtained; 2) The C substrate was immersed in 220 °C molten lithium in a vacuum furnace, kept at this temperature for 20 min, and then taken out and cooled to obtain a carbon-reinforced lithium-carbon composite electrode.

[0050] The performance of the obtained carbon-enhanced lithium-carbon composite electrode with lithium-philic properties was characterized.

[0051] Signs include: Specific capacity characterization and cycle stability (500 cycle retention rate), the above characterizations were carried out at current density of 0.1 A / g, 0.5 A / g and 2.0 A / g, respectively.

[0052] The characterization results are shown in the following table.

[0053]

[0054] From the above characterization results, it can be clearly seen that the electrochemical performance of the lithium-carbon electrode directly constructed with carbon nanotubes and metal lithium is much lower than that of the lithium-carbon composite electrode of the present invention. The specific capacity is similar to that of a conventional carbon electrode, because for the immersion plating of metal lithium, the affinity of the carrier itself with lithium is very limited. Compared with tin, directly loading metal lithium on the carbon carrier has low binding strength and poor affinity, and it is very easy for lithium to fall off during the cycle, thereby showing a cycle stability far lower than that of the composite electrode of the present invention.

[0055] Comparative Example 2 A commercially available high-performance lithium-carbon (graphite) composite electrode was subjected to the same performance characterization as in Example 1.

[0056] The characterization results are shown in the following table.

[0057]

[0058] From the above characterization results, the high-performance lithium-carbon composite electrodes currently available on the market can also show relatively good specific capacity, but only perform relatively well under low current density conditions. At the same time, they are unable to overcome the problem of poor cycle stability.

Claims

1. A method for preparing a carbon-enhanced lithium-carbon composite electrode having lithium-philic properties, characterized in that: The method comprises: 1) Prepare tin element on a carbon support to obtain a C-Sn support; 2) Using C-Sn carrier as raw material to make it into thin sheets or paper to obtain C-Sn matrix; 3) Immersing the C-Sn substrate into molten lithium in a protective atmosphere, leaving it to stand and heat preservation, then taking it out and cooling it to obtain a carbon-enhanced lithium-carbon composite electrode with lithium-philic properties; Step 1) The carbon carrier is micron-sized and / or nano-sized carbon tubes and / or carbon powder.

2. The method for preparing a carbon-enhanced lithium-carbon composite electrode having lithium-philic properties according to claim 1, characterized in that: Step 1) The method for preparing the tin element is a melt impregnation method and / or a chemical deposition method and / or an oxidation-reduction method; in: The melt impregnation process is as follows: in a protective atmosphere, a carbon carrier is added to molten tin, stirred and kept warm for 1 to 20 minutes, and then the carbon carrier is filtered out and cooled, so that the surface of the carbon carrier solidifies to form a tin element load to obtain a C-Sn carrier; The chemical deposition method is reduction chemical tin plating and / or disproportionation reaction chemical tin plating and / or immersion chemical tin plating and / or acid tin plating and / or alkaline tin plating; The redox process is as follows: immersing the carbon carrier into a tin salt solution, immersing under negative pressure for 30 to 90 minutes, filtering and transferring to a protective atmosphere for carbon thermal reduction reaction for 30 to 90 minutes, and then cooling to obtain a C-Sn carrier.

3. The method for preparing a carbon-enhanced lithium-carbon composite electrode having lithium-philic properties according to claim 1, characterized in that: Step 2) The raw material is manufactured into a sheet or paper form by using a papermaking method and / or a suction filtration method.

4. The method for preparing a carbon-enhanced lithium-carbon composite electrode having lithium-philic properties according to claim 1 or 3, characterized in that: Step 2) The thickness of the C-Sn substrate is ≤3 mm.

5. The method for preparing a carbon-enhanced lithium-carbon composite electrode having lithium-philic properties according to claim 1, characterized in that: Step 3) immersing the C-Sn substrate into molten lithium and keeping the temperature for 1 to 20 minutes.

6. A carbon-enhanced lithium-carbon composite electrode having lithium-philic properties obtained by the method of any one of claims 1 to 5.

7. The carbon-enhanced lithium-carbon composite electrode with lithium-philic properties according to claim 6, characterized in that: The composite electrode uses a carbon carrier to construct a two-dimensional and / or three-dimensional micro-nano structure, and a tin-lithium alloy is loaded on the basis of the micro-nano structure to form a cross-scale multi-dimensional structure.

Citation Information

Patent Citations

  • Method for preparing lithium metal battery negative electrode supported by carbon / tin composite substrate

    CN110299512A

  • Lithium-carbon composite material, lithium battery and preparation method

    CN110854380A

  • Preparation method of lithium-philic carbon nanotube paper and preparation method of composite metal lithium negative electrode

    CN112176771A

  • Metal lithium composite negative electrode capable of being used for secondary battery and preparation method of metal lithium composite negative electrode

    CN115832217A

  • Lightweight lithium / carbon composite electrode and preparation method and application thereof

    CN116845185A